2003
DOI: 10.1046/j.1524-4741.2003.09313.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Lobular Carcinoma in a Breast Hamartoma

Abstract: Hamartomas are uncommon benign breast neoplasms. We report the first case, to our knowledge, of invasive lobular carcinoma arising in a breast hamartoma. This case illustrates the importance of careful interpretation of the clinical and mammographic findings. A more aggressive approach toward the management of breast hamartomas is not justified when clinical and mammographic findings are consistent with classic hamartomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…Very rarely, it has also been reported that hamartomas develop into carcinoma (7). While an invasive lobular carcinoma is reported to develop in some publications, development of ductal carcinoma is the most frequently reported (15)(16)(17)(18)(19)(20)(21). Thus, once the diagnosis is established, an excision should be performed (Figure 1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Very rarely, it has also been reported that hamartomas develop into carcinoma (7). While an invasive lobular carcinoma is reported to develop in some publications, development of ductal carcinoma is the most frequently reported (15)(16)(17)(18)(19)(20)(21). Thus, once the diagnosis is established, an excision should be performed (Figure 1-3).…”
Section: Discussionmentioning
confidence: 99%
“…With the increased availability of screening mammography, radiologists are more likely to detect this benign lesion [1,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically concealed as fibroadenoma, it may be difficult to palpate because of its similarity to surrounding normal breast tissue [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Con frecuencia es un hallazgo en la mamografía y se cree que su verdadera incidencia es probablemente superior a la recogida en la literatura. Con la masificación del cribaje del cáncer mamario, los radiólogos son en la actualidad más susceptibles de encontrar este tipo de lesión tumoral benigna (2)(3)(4)(5)(6).…”
Section: Introductionunclassified